2010
DOI: 10.1177/0363546510382225
|View full text |Cite
|
Sign up to set email alerts
|

Second-Look Arthroscopic Findings After Repairs of Posterior Root Tears of the Medial Meniscus

Abstract: Complete healing was not observed in this retrospective case series of posterior horn meniscus repairs performed by 2 surgeons using a single technique. Further research is needed to clarify why all patients showed clinical improvement despite findings of incomplete or failed healing on second-look arthroscopy. Treatment modalities for managing posterior root tears of the medial meniscus require further investigation to determine their efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
220
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(259 citation statements)
references
References 35 publications
4
220
1
6
Order By: Relevance
“…Commensurate with recent interest in MMPRT fixation, several fixation studies have been conducted. [2][3][4] Pullout fixation is typically performed using simple stitches and tends to produce favorable results. However, some studies that have used simple stitches have not reported any reduction in meniscal extrusion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Commensurate with recent interest in MMPRT fixation, several fixation studies have been conducted. [2][3][4] Pullout fixation is typically performed using simple stitches and tends to produce favorable results. However, some studies that have used simple stitches have not reported any reduction in meniscal extrusion.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies that have used simple stitches have not reported any reduction in meniscal extrusion. 2,4,8 Furthermore, during second-look arthroscopy, cases of partial, incomplete, and failed healing, in addition to scar tissue, have been reported, 3 probably because of weak holding power and a small meniscus-bone contact area. In a comparative study of MMPRT fixation using simple or modified Mason-Allen stitches, the modified stitches were associated with significantly superior outcomes on magnetic resonance imaging, with respect to postoperative meniscal extrusion and healing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Seo et al [54] performed second look arthroscopies in 11 patients who underwent arthroscopic repair of the posterior root attachment at 13.4 mo postoperatively and in none of them had the repair healed. A study [55] evaluating healing after meniscal repair using artho-CT scan also found that posterior segment healing rate was lower compared to middle portion tears.…”
Section: Meniscal Repairmentioning
confidence: 99%